The night I flunked my field trip - "Winkler, Henry" (Walker: London, 2008)
When Hank Zipzer's class gets to spend a night on a replica sailing ship, Hank is psyched! Then he learns that he's going to be Captain's Assistant and the best school trip ever quickly turns into the worst one
Keywords: School field trips